Condom use and partnership intimacy among drug injectors and their sexual partners in Estonia. Issue 1 (4th November 2011) - Uusküla, Anneli; Abel-Ollo, Katri; Markina, Anna; McNutt, Louise-Anne; Heimer, Robert
Abstract : Objectives: Young age coupled with a high HIV prevalence among injection drug users (IDUs) and the prevalence of drug use in Eastern Europe can lead from an HIV epidemic concentrated among IDU to a self-sustained heterosexual HIV epidemic. Our objective was to explore the contexts of the prevention of sexual transmission of HIV among IDUs and their sexual partners and to provide insight into beliefs and behaviours related to condom use. Methods: The authors undertook in-depth qualitative interviews to explore narratives about experience of preventing sexual transmission of HIV among 27 individuals (15 current IDUs and 12 main sexual partners of IDUs) in Kohtla-Järve, Estonia. Results: The safe-sex 'norm' was not common and factors that tended to reduce condom use included valuing the relationship above health risks, established gender roles, perceptions that condoms distributed via harm reduction programmes were of low quality and the stigma attached to HIV status disclosure. HIV risk management strategies among participants included consistent condom use and serosorting but were countered by a fatalism that encompassed consciously subjecting oneself to the inevitability of HIV infection in an HIV-discordant sexual partnership. Conclusions: Qualitative methods can significantly contribute to the prevention of sexual transmission of HIV among and beyond IDUs by improving our understanding of risky behaviours and the reasons for such behaviours that can be incorporated into tailored public health interventions.